NÚMEROS RACIONAIS E A ALFABETIZAÇÃO MATEMÁTICA NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: DISCUTINDO POSSIBILIDADES A PARTIR DA RESOLUÇÃO DE PROBLEMAS - Viana, Luciana Carrion (2024)
This research is linked to the Teaching and Learning in Science and Mathematics Research Line of the Professional Master’s course of the Graduate Program in Science and Mathematics Teaching at the Franciscan University, and has as general objective to investigate the potentialities that a Didactic Sequence, elaborated in the principles of Mathematical Literacy and Problem Solving, has for teaching the concept of rational numbers in fractional form, for students of the fifth year of elementary school. Mathematical literacy in the early years is a fundamental process for children’s cognitive and academic development, providing the necessary foundations for the understanding and application of mathematical concepts throughout life. This dissertation proposed to explore the possibilities of the Problem Solving methodology, as a strategy to promote mathematical literacy, in a contextualized and meaningful way. For this, a qualitative study was conducted in a class of 5th grade elementary school, in a municipal public school of Santa Maria, so that a didactic sequence was developed, focusing on rational numbers, from the paradidatic book entitled "Pedrinho and the power of numbers: learning hygiene and mathematics in school". With this proposal, we sought to identify contributions such as the development of logical reasoning, creativity and problem solving ability. For data collection, two main sources were used: photographic records and student manuscripts records. For the analysis of data was used the principles of descriptive and explanatory research. With this research it was possible to verify that there is a great gap in the literacy process, both mathematical and in the mother tongue, given the great difficulty of interpretation of the proposed problems, as well as the reading itself. However, the analysis revealed the great engagement of students in the activities, indicating the enthusiasm to read the book paradidático, from the moment they saw its cover, actively reflecting the social issues addressed in the book. Another factor of great relevance, was the proposal of Problem Solving that provided collaborative discussions, in which students with greater ease of learning could help students with more difficulties, providing a possible increase in interest and understanding of mathematical concepts.